Has aggressive investing strategy performed? An insight from Malaysia listed companies - Kontesa, Maria; Lim, Emily Jia Chee; Brahmana, Rayenda Khresna (University of Merdeka Malang, 2019)
This study examines the role of aggressive investing strategy on firm performance for a sample of 514 listed firms in Malaysia from 2010 to 2017. In our first objective, we investigate the investing activism effect on firm performance by simultaneously controlling the firm characteristics and industry in our model. Our second objective is to test whether aggressive investing activism affects firm performance. Lastly, we want to investigate whether this aggressive investing may produce different results with different measures of performance. Our findings show that investment has significant effects on firm performance. Our research further indicates that companies with aggressive investing strategies had a better firm performance than compared to its peers. We test this theory using three different measures of aggressive investing strategies and substantiate this conclusion. Our research confirms the resource-based view theory and empirically proves that aggressive investments would result in better firm performance.JEL Classification: C23, D21, G31, L25DOI: https://doi.org/10.26905/jkdp.v23i3.3069